2005
DOI: 10.1002/jpln.200421381
|View full text |Cite
|
Sign up to set email alerts
|

Zusammenhang zwischen hydraulischer und mechanischer Bodenstabilität in Abhängigkeit von der Belastungsdauer

Abstract: In Untersuchungen zur Bodenverdichtung wird meist nur die direkte Beziehung zwischen der mechanischen Belastung und der Porenänderung, nicht hingegen die Interaktion zwischen mechanischen und hydraulischen Prozessen als Funktion der Zeitdauer der Belastung bzw. der Häufigkeit der Belastung betrachtet. In der vorliegenden Arbeit wird daher die Beziehung zwischen der Vorbelastung als Maß der mechanischen Stabilität und der Wasserspannungsänderung während einer Belastung analysiert. Die Untersuchungen wurden an g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Longer loading times were usually found to increase compaction effects, e.g. by Ghezzehei and Or (2001) and Fazekas and Horn (2005). This effect was attributed to the viscoelastic behaviour of the investigated soils, preventing to reach mechanical equilibration over short times.…”
Section: Discussionmentioning
confidence: 81%
“…Longer loading times were usually found to increase compaction effects, e.g. by Ghezzehei and Or (2001) and Fazekas and Horn (2005). This effect was attributed to the viscoelastic behaviour of the investigated soils, preventing to reach mechanical equilibration over short times.…”
Section: Discussionmentioning
confidence: 81%
“…However, soil compaction also leads to a shift in pore-space distribution (Becher, 1994;Riggert et al, 2017) whereby positive water pressures can be observed (Fazekas and Horn, 2005). Positive water pressures combined with shearing forces which occur due to the cone-shaped tip of the body of earthworms lead to a completely homogenization of soil aggregates, followed by swelling, and the blockage of smaller lateral side-pores.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out by Lebert et al (1989) and Fazekas & Horn (2005) showed differences in the values of the pre-consolidation pressure as well as the compressibility index. According to these authors, there was a reduction of the first and an increase in the values of the second indicator with the increase of the loading time, in static tests using consolidometers.…”
Section: Introductionmentioning
confidence: 93%